(3ecGJHI JPcQgs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s; (3eMeO Hf YeQ Hf CHj GdaJhM GdHZOGOj GdeGQOjfj, GHf GdeQGgs
(3ChdgG (B:s
(3cJGHi Edi Cgdi hENhGfi GdHQQg GdSGObjf hGdGUajGA GdWgGQ GdeMbjf EPG cGf def JPcQ hOYG s
(3BNQgG (B:s
(3hCf GSJhOY cGaJce ddg hGdLeGYI GdMGaXjf hgh MSHi hfYe GdfUjQ GdeYjf hSdGeg hUdhGJg Ydi QShdg GdSGOb GdGejf Edi LejY GdGee hGdMeO dehdGfG hMOg hGdTcQ dhdjg GdgGOi YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis